Poor Status of Vitamin D: A Survey of Area With Lowest Sunlight Radiation in Sichuan, China - Fan, Pianpian; Wang, Qin; Li, Jing; Lu, Chunyan; Xu, Yong; Cao, Hongyi; Xie, Xiaohua; Wu, Xueyan; Guo, Yanhong; Liu, Ting; Chen, Yan; Xu, Shen; et al. (Frontiers in Endocrinology, 2021)
Objective: Vitamin D plays an important role in bone and mineral metabolism. Ultraviolet B (UVB) is the primary determinant for vitamin D synthesis. However, population-based data of vitamin D status was sparse in areas with sunlight deprivation in China. This study aimed to assess serum 25-hydroxyvitamin D [25(OH)D] levels among adult women in Sichuan basin with the lowest sunlight radiation in China, and the associations with sunlight exposure and age. Methods: In the context of the same ethnicity, similar latitude and lifestyle in sunlight-limited basin and sunlight-abundant plateau, 1057 women in basin and 337 in plateau aged 29-95 years were included in this study, from November 2012 to February 2013. Daily sunlight exposure duration of previous month was obtained using questionnaires. Serum 25(OH)D was measured by enzyme-linked immunosorbent assay. Results: The prevalence of vitamin D severe deficiency [25(OH)D <30 nmol/L] and deficiency [30 ≤25(OH)D <50 nmol/L] was significantly higher in basin than plateau (21.85% vs. 10.09%, and 59.32% vs. 40.36%; P<0.0001). Women from basin exhibited lower serum 25(OH)D levels than those from plateau (40.66±15.62 vs. 52.54±19.94 nmol/L, P<0.0001). In basin, women more than 50 years old had higher 25(OH)D than younger counterparts, and 25(OH)D level of both the two groups was not associated with sunlight exposure duration. While in plateau, women younger than 60 years old had higher 25(OH)D than the older women. Furthermore, for those younger groups, women with long sunlight exposure (≥3 hours) had higher 25(OH)D concentration than those with short sunlight exposure (<3 hours). Serum PTH was negatively associated with 25(OH)D in basin, but not in plateau. Conclusions: Alarmingly high vitamin D deficiency was observed in women in sunlight-deprived basin in Sichuan. Only the vitamin D status of younger women from plateau with adequate solar radiation could benefit from sunlight exposure. Vitamin D supplementation and vitamin D-fortified food should be encouraged to improve vitamin D status for women living in sunlight-limited areas, or with old age.